Oxaliplatin Eluting CalliSpheres Microspheres for the Treatment of Unresectable or Recurrent Hepatocellular Carcinoma - Bi, Yonghua; Ren, Kewei; Ren, Jianzhuang; Ma, Ji; Han, Xinwei (Frontiers in Pharmacology, 2022)
Aim: Transarterial chemoembolization (TACE) has been widely used in unresectable and advanced hepatocellular carcinoma (HCC). However, no study reported the clinical outcomes of drug-eluting beads TACE (DEB-TACE) with oxaliplatin-eluting Callispheres microspheres in the treatment of HCC. We aim to report the preliminary outcomes of DEB-TACE loaded with oxaliplatin in patients with unresectable or recurrent HCC. Methods: From November 2019 and November 2021, 29 patients with unresectable or recurrent HCC were recruited from our department and treated by DEB-TACE loaded with oxaliplatin. The progression-free survival (PFS) was the primary end point. Disease control rate and safety were the secondary end points. Tumor response was investigated 1-, 3- and 6-month after DEB-TACE according to the response evaluation criteria in solid tumors (RECIST) criteria and the modified RECIST criteria (mRECIST) . Survival curve was generated with the Kaplan-Meier method. Results: A total of 49 DEB-TACE sessions were performed, with a technique success rate of 100%. The overall response rate and disease control rate were 52.4% and 95.2%, 64.7% and 76.5%, 54.5% and 63.3% respectively at 1, 3, and 6 months after DEB-TACE (mRECIST). The PFS was 5.9 months and the median overall survival was 18.8 months. The 6-, and 12-month overall survival rates were 82.5% and 67.5%, respectively, No treatment-related mortality or severe adverse events were observed. Minor complications were observed in 21 patients (72.4%),and abdominal pain (41.4%) was the most common treatment-related complication . Conclusion: DEB-TACE loaded with oxaliplatin-eluting Callispheres microspheres suggested a safe, feasible and efficacious palliative regimen in unresectable or recurrent HCC patients.